The encyclopedia of Philosophy - The Encyclopedia... (Macmillan Publishing Co., 1967)
tr, jil.1-2; 3-4; 5-6 = 1-4; jil. 7-8, index =. 1-3/stoc1, jil.[1-2] ;[3-4] ; [5-6] = c.1-4 , jil.[7-8, index]=c.1-3